Barriers to Employee-Driven Innovation: A Study of a Regional Medium-Sized Bakery. (August 2014) - Aaltonen, Satu; Hytti, Ulla
Innovativeness and employee-driven innovations in particular are important sources of competitiveness for small and medium-sized food companies. The fierce competition in the food industry is forcing these companies to increase their operational efficiency in order to compete with the large companies in the market. This paper investigates barriers to innovations in the bakery sector through a case study of a growth-oriented regional bakery. The study contributes to new contextualized knowledge of employee-driven innovation activity in small food production companies. It provides a nuanced understanding of how the manufacturing context of a bakery leads to specific constraints on innovative employee behaviour, and of how the context and the human, organizational and physical resources interact with employee-driven innovation activity.